1983
DOI: 10.1128/mcb.3.9.1567
|View full text |Cite
|
Sign up to set email alerts
|

Proteins tightly bound to HeLa cell DNA at nuclear matrix attachment sites.

Abstract: DNA-protein complexes have been isolated from HeLa cell nuclei and nuclear matrix preparations. Two proteins, 55 and 66 kilodaltons in size, remain bound to HeLa DNA after treatment at 80°C in 2% sodium dodecyl sulfate and purification by exclusion chromatography on Sepharose 2B-CL in the presence of 0.3% sodium dodecyl sulfate. These proteins appear to be tightly bound but not covalently linked to the DNA, and they are distributed over the DNA with an average spacing of 40 kilobase pairs. This spacing distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…One potential clue is provided by the fact that C1D binds to DNA in an extremely stable fashion, as evidenced by the fact that it remains DNA-associated even after rigorous extraction procedures. Highly stable nonhistone proteins that are bound to DNA tightly have been identified in various systems, including insects, plants, and mammalian cells (Krauth and Werner 1979;Capesius et al 1980;Bodnar et al 1983;Avramova and Tsanev 1987). Although the biological functions for these proteins are still largely obscure, it is noteworthy that some have been reported to be associated with highly repetitive DNA sequences and to be involved in targeting a subset of genomic DNA to the nuclear matrix (Neuer and Werner 1985;NeuerNitsche et al 1988;Werner and Neuer-Nitsche 1989;Pfutz et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…One potential clue is provided by the fact that C1D binds to DNA in an extremely stable fashion, as evidenced by the fact that it remains DNA-associated even after rigorous extraction procedures. Highly stable nonhistone proteins that are bound to DNA tightly have been identified in various systems, including insects, plants, and mammalian cells (Krauth and Werner 1979;Capesius et al 1980;Bodnar et al 1983;Avramova and Tsanev 1987). Although the biological functions for these proteins are still largely obscure, it is noteworthy that some have been reported to be associated with highly repetitive DNA sequences and to be involved in targeting a subset of genomic DNA to the nuclear matrix (Neuer and Werner 1985;NeuerNitsche et al 1988;Werner and Neuer-Nitsche 1989;Pfutz et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The overall alkylation level in rat mitochondrial DNA ex- posed to methylating N-nitroso compounds (N,N-dimethylnitrosamine, N-methyl-N-nitrosourea) exceeds that of rat nuclear DNA by a factor of s5 (Wunderlich et al, 1971;Wilkie and Evans, 1982 The fact that clustered O6-EtdGuo sites were only observed in DNA fragments contained in a fraction of DNA isolated by virtue of its association with specific polypeptides may be explained by two alternative hypotheses. (i) The tightly bound polypeptides found in chromosomal DNA (Bodnar et al, 1983;Krauth and Werner, 1979;Neuer et al, 1983;Werner et al, 1981a) may be involved in a nuclear structure and/or function which renders the vicinal DNA more accessible to the ethyldiazonium ions generated from EtNU (see, e.g., the putative mechanisms a -d mentioned above). (ii) It may be argued that by virtue of particular structural properties of its own, a small fraction of DNA might be more sensitive to ethylation by EtNU.…”
Section: Discussionmentioning
confidence: 99%
“…As previously shown, highly purified chromosomal DNA still contains distinct types of polypeptides (Bodnar et al, 1983;Krauth and Werner, 1979;Werner et al, 1981a) which are covalently bound to internal ends of DNA molecules (Neuer et al, 1983). DNA fragments containing such DNA-protein complexes may be essential constituents of higher order chromatin structures and/or be involved in the anchorage of DNA in nuclear structures (Bodnar et al, 1983;Werner et al, 1980Werner et al, , 1981a.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations